Urban Commoning: An Assessment of Its Aesthetic Dimension - Volont, Louis (2022)
The practice of urban commoning continues to tickle the imagination of activists and academics alike. Urban commoning’s aesthetic dimension, yet, has not been fully understood. This contribution seeks to fill such gap and approaches aesthetics in the literal sense: That which presents itself to sense perception. The article thus asks: To what extent may commoning practices that are dedicated to the disclosure of unheard voices (hence having an aesthetic dimension) shift urban power relations? This contribution takes its cue in Jacques Rancière’s theory of aesthetics and has the commoning experiment of Pension Almonde as its central case. Pension Almonde constituted a commons‐based, temporary occupation of a vacant social housing complex in Rotterdam, aimed specifically to undo the subordinate position of urban nomads and orphaned cultural initiatives. The article finally develops the distinction between a particular‐aesthetic dimension (making unheard voices merely perceptible) and a universal‐aesthetic dimension (shifting power relations) of urban commoning. Given the case’s lack of collective agency and external resonance, urban power relations remained in place.